Study of Water- and Organic-Soluble Extracts from Trichosanthes on Type 1 Diabetes Mellitus - Bo Zhang; Yanli Yuan; Jie Xin; Min Chen; Zhen Wang; Xinpeng Li; Tao Xue (Journal of Diabetes Research)
This study investigates the effects of the water-soluble and organic-soluble Trichosanthes extracts on the hyperglycemic condition in streptozotocin- (STZ-) induced diabetic rats. The blood glucose levels, body weights, water intake, and urine volumes of rats in different experimental groups were monitored throughout the experiment, and the results obtained indicate that the two extracts can effectively reduce blood sugar levels, increase body weights, and improve water intake and urine volumes in diabetic rats. Based on blood biochemical analyses, the two extracts play an important role in regulating the diabetes-induced lipid metabolism disorder, increasing the levels of insulin and C-peptide, and alleviating the symptoms of diabetes. The variation in the liver glycogen contents of the water-soluble fraction and ethanol fraction groups suggests that the mechanisms underlying the hypoglycemic effects of the two extracts are different. Indeed, the water-soluble fraction alleviates diabetes symptoms in rats mainly by antioxidative activity, unlike the ethanol fraction.